Consumer Preference on Paid Game Microtransaction - Adji, Mahesa Nararya; Chua, David; Kainama, Nathaniel; Feranita, Feranita (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
Online gaming has become prevalent with the rise of the internet availability, where the gaming industry is experiencing a shift in business model in the last decade. The new model of microtransaction is to make players pay for extra content and advantages to compete against other players. In this paper, we aim at finding out what the consumer preference on microtransaction in paid game. Mode, Price, Genre, Microtransaction, and Payment Method are the preferences used as benchmark for this research that influences decision making for players. To better understand the characters of the players, cluster analysis is used to group players who have similar preferences with their respective preferences.